The impact of health education videos on general public's mental health and behavior during COVID-19 - Qian Yang; Zhihua Wu; Ying Xie; Xiaohua Xiao; Jinnan Wu; Tian Sang; Kejun Zhang; Haidong Song; Xifeng Wu; Xin Xu (BMC, 2021)
Abstract Background COVID-19 has seriously affected people's mental health and changed their behaviors. Previous studies for mental state and behavior promotion only targeted limited people or were not suitable for daily activity restrictions. Therefore, we decided to explore the effect of health education videos on people's mental state and health-related behaviors. Methods Based on WeChat, QQ, and other social media, we conducted an online survey by snowball sampling. Spearman's non-parametric method was used to analyze the correlation related to mental health problems and health-related behaviors. Besides, we used binary logistic regression analyses to examine mental health problems and health-related behaviors' predictors. We performed SPSS macro PROCESS (model 4 and model 6) to analyze mediation relationships between exposure to health education videos and depression/anxiety/health-related behaviors. These models were regarded as exploratory. Results Binary logistic regression analyses indicated that people who watched the health education videos were more likely to wear masks (OR 1.15, p < 0.001), disinfect (OR 1.26, p < 0.001), and take temperature (OR 1.37, p < 0.001). With higher level of posttraumatic growth (PTG) or perceived social support (PSS), people had lower percentage of depression (For PSS, OR 0.98, p < 0.001; For PTG, OR 0.98, p < 0.01) and anxiety (For PSS, OR 0.98, p < 0.001; For PTG, OR 0.98, p = 0.01) and better health behaviors. The serial multiple-mediation model supported the positive indirect effects of exposure to health education videos on the depression and three health-related behaviors through PSS and PTG (Depression: B[SE] =  − 0.0046 [0.0021], 95% CI − 0.0098, − 0.0012; Mask-wearing: B[SE] = 0.0051 [0.0023], 95% CI 0.0015, 0.0010; Disinfection: B[SE] = 0.0059 [0.0024], 95% CI 0.0024, 0.0012; Temperature-taking: B[SE] = 0.0067 [0.0026], 95% CI 0.0023, 0.0013). Conclusion Exposure to health education videos can improve people's self-perceived social support and inner growth and help them cope with the adverse impact of public health emergencies with better mental health and health-related behaviors.